Detection and Analysis Tool Wear of Carbide Flat End Mills 2T, 3T, 4T for Surface-Rough Machining by Third Wave AdvantEdgeTM Software Simulation. - Siswanto, Dony Irvan; , Dr. Agus Dwi Anggono; , Zou Ye (2016)
ABSTRACT Surface rough-machining is one of the important process before finishing process. For the finding the best result of rough-machining's quality criteria, least machining time and least remaining volume without making worse of tool wear after roughing so need detection and analysis optimum parameter proses without ignoring tool wear's aspect. Cemented Carbide flat End-mill with 2, 3, 4 Flutes used as the main case parameter study with Al 7075 T6 as the workpiece materials, by calculation and bring it to Third Wave Advant EdgeTM Systems Software simulation some data become recommendation production parameters as the final conclusion. Proses kekasaran permukaan merupakan salah satu proses penting sebelum proses finishing. Untuk menemukan hasil terbaik dari kriteria kualitas kasar-mesin ini, waktu mesin setidaknya dan volume tersisa sedikit tanpa membuat lebih buruk memakai alat setelah hidup seadanya sehingga perlu deteksi dan analisis optimum Proses parameter tanpa mengabaikan aspek memakai alat ini. Semen Carbide datar End-pabrik dengan 2, 3, 4 Flutes digunakan sebagai studi parameter kasus utama dengan Al 7075 T6 sebagai bahan benda kerja, dengan perhitungan dan membawanya ke simulasi Gelombang Ketiga Advant EdgeTM Sistem Software beberapa data menjadi parameter produksi rekomendasi sebagai kesimpulan akhir. Key words: Rough-machining (proses kekasaran permukaan), Cemented Carbide End-mill (Karbida Endmill), Al 7075 T6, Third Wave Advant EdgeTM.